2021
DOI: 10.3390/jpm11060449
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Visual Prognosis in Diabetic Macular Oedema

Abstract: Diabetic macular oedema (DMO) is an important cause of moderate vision loss in people with diabetes. Advances in imaging technology have shown that a significant proportion of patients with DMO respond sub-optimally to existing treatment options. Identifying associations and predictors of response before treatment is initiated may help in explaining visual prognosis to patients and aid the development of personalized treatment strategies. Imaging features, such as central subfoveal thickness, photoreceptor int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 119 publications
(134 reference statements)
1
6
0
Order By: Relevance
“…Therefore, it is necessary to study further the relationship between the detailed characteristics of imaging and the prognosis. Many DME-related biomarkers based on SD-OCT imaging, such as CST, choroidal thickness, HRD, HE, SRF, IRC, EZ or ELM rupture, and DRIL, have been proven to be general prognostic biomarkers of anatomical or functional outcomes [13][14][15][16][17]. In the future, the information parameters of macular perfusion provided by OCTA will be further used in the evaluation system [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to study further the relationship between the detailed characteristics of imaging and the prognosis. Many DME-related biomarkers based on SD-OCT imaging, such as CST, choroidal thickness, HRD, HE, SRF, IRC, EZ or ELM rupture, and DRIL, have been proven to be general prognostic biomarkers of anatomical or functional outcomes [13][14][15][16][17]. In the future, the information parameters of macular perfusion provided by OCTA will be further used in the evaluation system [18].…”
Section: Discussionmentioning
confidence: 99%
“…A normal choroidal function is necessary for metabolic support of the outer retina (28). Studies on SFCT in eyes with DME have yielded inconsistent results (29). However, regarding the role of the choroid in the pathophysiology of DME, it is suggested that decreased subfoveal choroidal circulation in people with retinopathy secondary to type 2 DM (especially in eyes with DME) could lead to relative hypoxia in the outer retina and retinal pigment epithelial (RPE), which, in turn, could result in increased permeability of the outer blood-retinal barrier and drainage dysfunction of RPE (2).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic DME can also lead to structural disorganization of retinal inner layers (DRIL) due to glial and neuronal cell death. DRIL is a good predictor of visual outcome [188]. Another correlation of MGC in DME has been related to the correlation of poor visual acuity and the destruction of Müller cell cones [189].…”
Section: Müller Cells In Drmentioning
confidence: 99%